2021
DOI: 10.3389/fnins.2021.642047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multisession Anodal Electrical Stimulation of the Auditory Cortex on Temporary Noise-Induced Hearing Loss in the Rat

Abstract: The protective effect of the efferent system against acoustic trauma (AT) has been shown by several experimental approaches, including damage to one ear, sectioning of the olivocochlear bundle (OCB) in the floor of the IV ventricle, and knock-in mice overexpressing outer hair cell (OHC) cholinergic receptors, among others. Such effects have been related to changes in the regulation of the cholinergic efferent system and in cochlear amplification, which ultimately reverse upon protective hearing suppression. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Recordings performed in rats after anodal DC stimulation with trains of pulses delivered to the skin, skull, and dura have demonstrated that voltage declines quickly in the brain towards a low global value of conductivity of 0.57 S/m (Asan et al, 2019 ). Due to physical interactions between electric currents and neural tissues, DC stimulation induces a limited activation of the cortex, which is less than 1 mm deep, as previously shown in rat animal models (Colmenárez-Raga et al, 2019 ; Díaz et al, 2021 ). Alternating current (AC) stimulation, in contrast, does not induce polarizing effects but activates neuronal networks via rhythmic stimulation by synchronizing their endogenous neurophysiological activities (Fröhlich and McCormick, 2010 ; Zaehle et al, 2010 ; Reato et al, 2013 ; Abd Hamid et al, 2015 ; Vossen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 73%
“…Recordings performed in rats after anodal DC stimulation with trains of pulses delivered to the skin, skull, and dura have demonstrated that voltage declines quickly in the brain towards a low global value of conductivity of 0.57 S/m (Asan et al, 2019 ). Due to physical interactions between electric currents and neural tissues, DC stimulation induces a limited activation of the cortex, which is less than 1 mm deep, as previously shown in rat animal models (Colmenárez-Raga et al, 2019 ; Díaz et al, 2021 ). Alternating current (AC) stimulation, in contrast, does not induce polarizing effects but activates neuronal networks via rhythmic stimulation by synchronizing their endogenous neurophysiological activities (Fröhlich and McCormick, 2010 ; Zaehle et al, 2010 ; Reato et al, 2013 ; Abd Hamid et al, 2015 ; Vossen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 73%
“…Intense sounds have been observed to cause temporary threshold shifts in humans and other mammals, as well as to have an effect on cochlear microphonics. The transient nature of this noise-induced hearing loss indicates an underlying protective mechanism against permanent damage ( Clark, 1991 ; Melnick, 1991 ; Patuzzi, 2002 ; Lichtenhan and Chertoff, 2008 ; Díaz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The efferent system has been linked to the auditory system’s inherent otoprotective capacity ( Handrock and Zeisberg, 1982 ; Reiter and Liberman, 1995 ; Maison and Liberman, 2000 ; Taranda et al, 2009 ; Boero et al, 2018 ; Díaz et al, 2021 ; Ohata et al, 2021 ). A number of studies have detected higher levels of noise-induced damage (hair cell and synaptic deterioration) in subjects with severed efferent innervation ( Zheng et al, 2000 ; Maison et al, 2002 , 2013 ; Kujawa and Liberman, 2009 ; Taranda et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%